The store eaudiobook - Patterson, James (2017)
The Store doesn't just want your money—it wants your soul. BONUS: Includes the first-time-in-print novel The End ! THE STORE IS WATCHING YOU. Jacob and Megan Brandeis have gotten jobs with the mega-successful, ultra-secretive Store. Seems perfect. Seems safe. But their lives are about to become anything but perfect, anything but safe. ALWAYS WATCHING. Especially since Jacob and Megan have a dark secret of their own. They're writing a book that will expose the Store—a forbidden book, a dangerous book. ALWAYS. And if the Store finds out, there's only one thing Jacob, Megan and their kids can do—run for their bloody lives. Which is probably impossible, because— THE STORE IS ALWAYS WATCHING.